2017
DOI: 10.1080/00140139.2017.1397201
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional shapes of underground coal miners’ feet do not match the internal dimensions of their work boots

Abstract: . (2018). The three-dimensional shapes of underground coal miners' feet do not match the internal dimensions of their work boots. Ergonomics: an international journal of research and practice in human factors and ergonomics, 61 (4), 588-602.The three-dimensional shapes of underground coal miners' feet do not match the internal dimensions of their work boots AbstractMining work boots provide an interface between the foot and the ground, protecting and supporting miners' feet during lengthy coal mining shifts. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
(45 reference statements)
0
16
0
Order By: Relevance
“…Incorrect sized footwear defined as foot length at least 2 mm difference between foot length and reported footwear size dimensions. • 110 women (48.5%) and 119 men (69.2%) wore incorrect size footwear (> 2 mm difference) based on foot and shoe length • 29 women (12.8%) and 57 men (31.1%) were wearing footwear at least 1 cm longer than their feet • 1 (0.6%) man was wearing shoes shorter than his feet • There was a significant association between men and wearing incorrectly sized footwear • 19 women or 55.9% of all women with diabetes and 31 or 81.6% of all men with diabetes were wearing incorrectly sized footwear • Incorrectly sized footwear was associated with ankle pain in women Dobson et al [ 24 ] 270 participants, all men, mean age 38.3 ± 9.8 yrs., height 178.9 ± 5.7 cm, weight 93.2 ± 12.5 kg. All participants were underground coal miners.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorrect sized footwear defined as foot length at least 2 mm difference between foot length and reported footwear size dimensions. • 110 women (48.5%) and 119 men (69.2%) wore incorrect size footwear (> 2 mm difference) based on foot and shoe length • 29 women (12.8%) and 57 men (31.1%) were wearing footwear at least 1 cm longer than their feet • 1 (0.6%) man was wearing shoes shorter than his feet • There was a significant association between men and wearing incorrectly sized footwear • 19 women or 55.9% of all women with diabetes and 31 or 81.6% of all men with diabetes were wearing incorrectly sized footwear • Incorrectly sized footwear was associated with ankle pain in women Dobson et al [ 24 ] 270 participants, all men, mean age 38.3 ± 9.8 yrs., height 178.9 ± 5.7 cm, weight 93.2 ± 12.5 kg. All participants were underground coal miners.…”
Section: Resultsmentioning
confidence: 99%
“…Specific ethnic groups were examined in three studies including participants of Japanese [ 21 ], Thai [ 19 ] or Singaporean [ 26 ] ethnicity. Finally, four studies recruited specific populations [ 24 , 25 , 30 , 31 ], including war veterans [ 25 ], underground coal miners [ 24 ], rock climbers [ 30 ] and three different population groups from New York City (a foot specialist private practice, an academic diabetic foot and ankle clinic, and a charity centre serving homeless people) [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the current research team's findings on the biomechanical impact of work boots, another team of researchers from the University of Wollongong, Australia have addressed the biomechanical and psychological impact of mining work boots [18][19][20][21][22][23]. Additionally, similar to the current study, previous research has used both postural sway and EMG measures to compare footwear types in standing tasks (barefoot, stable control shoes, and unstable shoes) [24].…”
Section: Introductionmentioning
confidence: 86%
“…Dobson et al [11] report that 62.3% of miners believed that their foot and ankle pain was related to their work boots. One explanation for this is that miners may be wearing boots that are longer than their feet, possibly because boots in their correct length are too narrow [27]. Dobson et al [28] concluded that traditional tting methods based on foot length were insu cient when tting miners.…”
Section: Footwear T and Comfortmentioning
confidence: 99%